2005
DOI: 10.1161/circulationaha.104.473629
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Heart Valves

Abstract: Background-Tissue-engineered or decellularized heart valves have already been implanted in humans or are currently approaching the clinical setting. The aim of this study was to examine the migratory response of human monocytic cells toward decellularized porcine and human heart valves, a pivotal step in the early immunologic reaction. Methods and Results-Porcine and human pulmonary valve conduits were decellularized, and migration of U-937 monocytic cells toward extracted heart valve proteins was examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…and type I collagen patches in the peritoneum cavity suggest that treatment with detergents makes the valve matrix more immunogenic, probably due to fine molecular alterations of the ECM system (publication in preparation). Using in vitro assays, Rieder et al ascertained that decellularized porcine pulmonary valve conduits are able to attract more monocytic cells than their human counterparts [39]. The same group also demonstrated that human polymorphonuclear leukocyte activation, subsequent to the contact of decellularized porcine matrices with human plasma, can be blocked by inhibitory elements extracted in the decellularization process [40], thus suggesting that an appropriate matching of the host (scaffold) to the donor (patient' s cells) is of paramount importance for the successful outcome of tissue engineering experiments.…”
Section: Discussionmentioning
confidence: 99%
“…and type I collagen patches in the peritoneum cavity suggest that treatment with detergents makes the valve matrix more immunogenic, probably due to fine molecular alterations of the ECM system (publication in preparation). Using in vitro assays, Rieder et al ascertained that decellularized porcine pulmonary valve conduits are able to attract more monocytic cells than their human counterparts [39]. The same group also demonstrated that human polymorphonuclear leukocyte activation, subsequent to the contact of decellularized porcine matrices with human plasma, can be blocked by inhibitory elements extracted in the decellularization process [40], thus suggesting that an appropriate matching of the host (scaffold) to the donor (patient' s cells) is of paramount importance for the successful outcome of tissue engineering experiments.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because of higher immune histocompatibility, comparable anatomic geometry, and structure, allogeneic scaffolds might be used successfully for TE despite the limited availability of human material. 5,9 The need for repopulation of valve scaffolds either in vitro or in vivo and the choice of cells is, however, still controversially discussed. 3-5,8 -11 Efficient tissue regeneration has been obtained by repopulation of biological decellularized scaffolds with interstitial cells in vivo.…”
mentioning
confidence: 99%
“…However, PTGs were significantly higher than the preoperative gradients and the short-term nature of this event precludes the genesis of a pathological stenosis. It is likely that PTG modification may depend on mechanical factors, such as anatomy of aortic root, patient-prosthesis mismatch, or pressure recovery, and biological factors, such as infection, coagulation, inflammation, cell repopulation, and ECM synthesis [28,29]. Of interest, an in vitro study demonstrated that TRICOL-treated valves showed lower gradients than in controls (non-decellularized, native valves) [17].…”
Section: Discussionmentioning
confidence: 99%